Immanuel Kant - Höffe, Otfried (Albany : State University of New York Press, 1994)
In this book, Hoffe gives a clear, understandable description of Kant's philosophical development and influence, and he sets forth Kant's main ideas from the Critique of Pure Reason and the ethics to the philosophy of law, history, religion, and art. In his critical treatment, Hoffe shows why Kant's philosophy continues to be relevant and challenging to us today.
The pre-critial period -- The critical transcendental philosophy -- The project of a transcendental critique of reason -- The transcendental aesthetic -- The analytic of concepts -- The analytic of principles -- The transcendental dialectic -- The critique of practical reason -- Political philosophy -- History as the progress of law -- The religion of practical reason -- The critique of judgment -- Reception, further development, and criticism of Kant's ideas.
Includes bibliographical references (pages 257-278) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Kant, Immanuel, -- 1724-1804.; Kant, Immanuel, -- 1724-1804; PHILOSOPHY -- History & Surveys -- Modern